2014
DOI: 10.1021/ja508094h
|View full text |Cite
|
Sign up to set email alerts
|

Metal-to-Metal Electron Transfer in Co/Fe Prussian Blue Molecular Analogues: The Ultimate Miniaturization

Abstract: Co/Fe Prussian Blue analogues are known to display both thermally and light induced electron transfer attributed to the switching between diamagnetic {Fe(II)LS(μ-CN)Co(III)LS} and paramagnetic {Fe(III)LS(μ-CN)Co(II)HS} pairs (LS = low spin; HS = high spin). In this work, a dinuclear cyanido-bridged Co/Fe complex, the smallest {Fe(μ-CN)Co} moiety at the origin of the remarkable physical properties of these systems, has been designed by a rational building-block approach. Combined structural, spectroscopic, magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
195
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(207 citation statements)
references
References 32 publications
8
195
0
4
Order By: Relevance
“…3 days versus 10 years). Subsequent work by us and also several other research groups has shown that di-, 9 tri-, 10 tetra-, 11 penta, 6 hexa-, 12 tetradecanuclear 13 complexes and 1-D coordination polymers 14 also display comparable photophysical properties, which are highly sensitive to chosen ancillary ligands and their solid state intermolecular environments.…”
Section: ■ Introductionmentioning
confidence: 92%
“…3 days versus 10 years). Subsequent work by us and also several other research groups has shown that di-, 9 tri-, 10 tetra-, 11 penta, 6 hexa-, 12 tetradecanuclear 13 complexes and 1-D coordination polymers 14 also display comparable photophysical properties, which are highly sensitive to chosen ancillary ligands and their solid state intermolecular environments.…”
Section: ■ Introductionmentioning
confidence: 92%
“…Recently various multinuclear cyanide-bridged FeCo clusters exhibiting thermal and photoinduced charge transfers have also been synthesized [73][74][75][76][77][78] . The charge transfer process of FeCo compounds is expressed through a reversible phase transition between low-temperature phase with Fe II LS(S=0) -CN-Co III LS(S=0) and a high-temperature phase with Fe III LS(S=1/2) -CN-Co II HS(S=3/2) (Fig.…”
Section: Coupled Charge Transfer and Spin Transitionmentioning
confidence: 99%
“…22 Alternatively, spin transitions can also be induced by metal-to-ligand charge transfer, which is well-known in cobalt/dioxolene chemistry for example (eq 2; cat = catecholate, sq  = semiquinonate):…”
Section: Spin-state Switches In Molecular Materials Chemistrymentioning
confidence: 99%